2016
DOI: 10.1186/s12893-016-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

The bicipital groove as a landmark for reconstruction of complex proximal humeral fractures with hybrid double plate osteosynthesis

Abstract: BackgroundComplex proximal humerus fractures with metaphyseal comminution remain challenging regarding reduction and stability. In most fracture patterns the hard bone of the bicipital groove remains intact. In this case series, we describe a novel technique of hybrid double plate osteosynthesis of complex proximal humerus fractures with metaphyseal comminution.MethodsIn randomly chosen shoulder specimens and synthetic bones, pilot studies for evaluation of the feasibility of the technique were performed. Betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
0
26
0
2
Order By: Relevance
“…The study by Theopold et al describes a technique which combines the classical locking plate with an in-verted anterior third-tubular plate. Here, the bicipital groove is used as an anatomic landmark [29].…”
Section: Proximal Humerusmentioning
confidence: 99%
“…The study by Theopold et al describes a technique which combines the classical locking plate with an in-verted anterior third-tubular plate. Here, the bicipital groove is used as an anatomic landmark [29].…”
Section: Proximal Humerusmentioning
confidence: 99%
“…These findings stand in contrast to past investigations which compared surgical and non-surgical treatments of Neer class 3 or 4 partial fractures and found no significant differences in treatment outcomes between the two methods. Other studies showed that there were no differences between locking plate and semijoint osteoplasties [22,23].…”
Section: Discussionmentioning
confidence: 95%
“…The only known, currently available clinical work with results after DPO with lateral angle-stable plate and additional anterior plate dates from 2016 by Theopold et al [19]. Seven of ten patients who underwent DPO for complex proximal humerus fractures were clinically evaluated.…”
Section: Proximal Humerusmentioning
confidence: 99%